The synergy of Calotropis gigantea and Cresscentia cujete plant extracts as an inhibitor of egg hatching and antifeedant against Spodoptera frugiperda. Issue 2 (July 2021) - Aprialty, A S; Sjam, S; Dewi, V S; Agustina, Y E
Abstract: Spodoptera frugiperda is an invasive pest that has spread in various countries including Indonesia. S. frugiperda has many hosts but a high interest in maize. This study for determining the ability of Calotropis gigantea extract, Cresscentia cujete extract and mixed extracts in inhibiting the ability of S. frugiperda eggs to hatch and inhibiting the eating activity of S. frugiperda . The research has been done at the Pesticides and Natural Materials Laboratory, Faculty of Agriculture, Hasanuddin University. Observations were carried out by examination various concentrations (2.5%, 5%, 7.5%, and 10%) extracts of C. gigantea and C. cujete, while mixed extract with a concentration of 7.5% on the ovicidal ability and feeding inhibition of S. frugiperda larvae. The results showed that treatment with a concentration of 10% C. gigantea extract had an ovicidal effect percentage of 74.58% while the antifeedant percentage was 64.40%. Treatment extract of C. cujete with a concentration of 10% had an ovicidal effect percentage of 90.99% while the antifeedant percentage was 70.05%. Treatment with mixed extract with a concentration of 7.5% had an ovicidal effect percentage of 91.7% while the antifeedant percentage was 85.26%. The conclusion is the existence synergy between C. gigantea and C. cujete extracts had showed that the ovicidal effect and antifeedant activity will be even higher to S. frugiperda .